Virtual Reality and Symptoms Management of Anxiety, Depression, Fatigue, and Pain: A Systematic Review - Androniki Ioannou BSc, MSc, PhD; Evridiki Papastavrou MSc, PhD; Marios N. Avraamides PhD; Andreas Charalambous MSc, PhD, RN (SAGE Publishing, 2020)
In recent years, virtual reality (VR) has become an interesting alternative to traditional exposure-based therapies for many symptoms. VR involves immersion in a computer-generated virtual environment that minimizes avoidance and facilitates emotional processing. The objective of this systematic review is to evaluate evidence on the intervention effect of VR on anxiety, depression, fatigue, and pain. The research strategy of this systematic review included three electronic databases (MEDLINE/PubMed, Cochrane Library, and ScienceDirect) based on predetermined inclusion and exclusion criteria. Published quantitative studies from 2000 to 2020 were identified, which examined the effect of VR intervention on four different symptoms related to symptoms experienced by cancer patients. Quality assessments, data extractions, and analysis were completed on all included studies. A total of 882 titles and abstracts were screened, and 23 studies were included in the review. The studies were grouped according to the symptoms: anxiety and depression, fatigue, and pain. The review showed that VR intervention is more effective compared with the control (i.e., standard care) for anxiety, depression, fatigue, and pain. VR can reduce effectively these symptoms in different contexts and diseases, including cancer. The evidence suggests that there is value in exploring this intervention as a potential crossover treatment for these symptoms in patients. This study contributes to evidence that distraction is an effective symptom management mechanism. The findings are congruent with the theoretical framework, supporting the premise that VR, as an emotion-focused distraction intervention, decreases the severity of these symptoms.